Online education strategies in the cardiac rehabilitation of patients with coronary heart disease. - Cui, Shanshan; Pang, Xin; Feng, Cuina; Wang, Shiqi; Li, Xuefei (Medicina (Buenos Aires))
Introduction: The objective of this study was to inves tigate the impact of a blended learning strategy, utilizing the Xuexitong online educational platform, on cardiac rehabilitation (CR) for patients with coronary heart dis ease (CHD) following hospital discharge Materials and methods: Seventy CHD patients dis charged from Hebei University Affiliated Hospital be tween July 2022 and January 2023 were randomly divided into blended and conventional education groups. Both received routine CR education before discharge. Post - discharge, the conventional group got education and supervision via WeChat, and the blended group used Xuexitong for blended education. The study compared risk factor control, cardiovascular events, quality of life, and CR compliance between the two groups pre - and post - intervention. Results: After intervention, the blended education group had a higher risk factor control rate (blood pres sure 91.4%, LDL cholesterol 91.4%, glycemia 88.6%) than the conventional group (60%, 68.6%, 51.4% respectively, p<0.01). Cardiovascular events occurred in 5 (14.3%) in the blended group and 15 (43%) in the conventional group, with a relative risk of 0.33 (0.14-0.82). The blend ed group's quality of life (81 (76-85)) was higher than the conventional group's (62 (58-66), P<0.001). Also, the blended group's CR compliance (19 (17-20)) was higher than the conventional group's (15 (13-16)) during the intervention (P<0.001). Conclusion: Applying a blended patient education strategy based on Xuexitong for patients with CHD after discharge can effectively control risk factors, reduce adverse cardiovascular events, improve quality of life, and enhance CR compliance.